Artificial Intelligence (AI) in Language and Science Learning in Elementary Schools: Teacher Perceptions and Solutions - Nur Samsiyah; V. Teguh Suharto; Chafit Ulya (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The research is motivated by the existence of teachers who still do not use technology in learning, as evidenced by research that has been conducted by several studies. The purpose of this study is to describe artificial intelligence in learning Language and Science in elementary schools in terms of teacher perceptions and Solutions. This research is a qualitative study with a case study type. The subjects of the study were elementary school teachers in Madiun district. The research location is in Madiun district, East Java. The number of respondents was 108 teachers who had filled out the questionnaire. Data was collected using data collection techniques in the form of questionnaires, observations, and interviews. The instruments used were questionnaire sheets, observation sheets, and open questions. Indicators in the study were the use of artificial intelligence, design, and types. Data analysis was carried out starting from data reduction. The results of the study showed that the perception of teachers in using artificial intelligence was 84 people who had used artificial intelligence. Teachers use artificial intelligence to get information, copy, and update in teaching. The type of artificial intelligence most widely used by Canva teachers was 96 people, while other types used were Powtoon, sway, and Google Classroom. The solution can be done by improving digital competence, improving the quality of education providing training in small groups, and continuing with the simplest artificial intelligence practice. Mentoring and evaluation of workshop results need to be done so that the continuation of the training program can be known.